Innovating Healthcare The Role of Political, Managerial and Clinical Leadership - Storey, John (Routledge Studies in Health Management, 2020)
Why is there a need to 'innovate healthcare'? The basic reason stems from the sheer scale of the challenges now facing healthcare provision in the UK and across many other countries. The aim of this book is to interrogate past and current attempts to innovate in this arena and to draw-out the key lessons. Innovating Healthcare: The Role of Political, Managerial and Clinical Leadership presents the latest state of knowledge based on original data from a series of NIHR-funded research projects set in the context of a review of extensive secondary research. The book draws upon first-person verbatim accounts of change attempts made by doctors and other clinicians as well as upon research findings about the roles played by policy-makers and managers. The analysis draws upon theory and practice in leadership, innovation and institution-building. The mutually-reinforcing contributions of political, managerial and clinical leadership are at the core of the investigative narrative. This book will be of interest to students and researchers, clinicians and managers in the health and care sectors as well as policy-makers. While the focus in on healthcare, the book has wider relevance for students of management, leadership, innovation and organizational studies.